Strategies for handling ethical problems in sudden and unexpected death - Rejnö, Åsa (Nursing ethics, 2013)
How ethical praxis is shaped by different contexts and situations has not been widely studied. We performed a follow-up study on stroke team members’ experiences of ethical problems and how the teams managed the situation when caring for patients faced with sudden and unexpected death from stroke. A number of ways for handling ethical problems emerged, which we have now explored further. Data were collected through a three-part form used as base for individual interviews with 15 stroke team members and analyzed using both quantitative and qualitative content analysis. In the analysis, the approaches in the form were condensed into strategies, and the two different ways those strategies were preferred and used by the team members were shown. Hindrances perceived by the team members to impede them from working the preferred way were also revealed and grouped into eight categories.